Addressing the Scalability Trilemma for Mass Market Gamichain Applications - Ayun Maduwinarti; Muhamad Ikhsan Mustopa; Henry Zainarthur (Pandawan Sejahtera Indonesia, 2026)
The convergence of blockchain technology and gamification has led to the emergence of Gamichain ecosystems that are increasingly adopted in digital business environments to enhance user engagement, transparency, and value exchange. Despite this potential, the blockchain scalability trilemma, which involves trade offs between decentralization, security, and scalability, remains a critical barrier to the mass market adoption of Gamichain applications. This study aims to analyze how the scalability trilemma influences the feasibility of large scale Gamichain systems and to identify architectural strategies that enable high frequency transactions and large user participation while preserving system trust. A qualitative conceptual approach supported by comparative case analysis is employed, examining representative implementations such as Axie Infinity, StepN, and Polygon based gaming platforms. The analysis evaluates existing scalability solutions including Layer 2 rollups, sharding mechanisms, and hybrid off chain and on chain architectures across key dimensions of security, decentralization, transaction throughput, and user experience. The results indicate that Layer 2 and hybrid architectures provide the most viable balance for mass market Gamichain deployment, as they significantly improve performance efficiency and transaction cost without substantially undermining decentralization and security guarantees. This study contributes an applied evaluation framework that connects blockchain scalability discourse with practical digital business requirements. In conclusion, scalable Gamichain adoption depends not only on technical scalability solutions but also on strategic architectural alignment with user experience optimization, regulatory readiness, and sustainable digital innovation, thereby supporting broader participation in the global digital economy.